Logos and pathos in the paintings of Sandro Botticelli - Giuseppe Di Giacomo (Hygeia Press di Corridori Marinella, 2019)
The Author focuses on the representation of the anatomical defects detected in Botticelli's paintings as a process of individualization of the sitter. It seems coherent with the non idealistic patterns brought about by the newest acquaintance with the Flemish painture, pursued in Italy thanks to the innovative style of Antonello da Messina. It is seen as closely related with the dramatization and the emotional effect of the portrayal, a challenge between logos and pathos, between drawing and color, rationale and emotional.